2001
DOI: 10.1128/jvi.75.6.2957-2971.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of the Basic Domain of Human Immunodeficiency Virus Type 1 Rev for a Polyarginine Stretch Expands the RNA Binding Specificity, and a Minimal Arginine Cluster Is Required for Optimal RRE RNA Binding Affinity, Nuclear Accumulation, and trans -Activation

Abstract: The Rev regulatory protein of human immunodeficiency virus (HIV) facilitates the nuclear export of unspliced and partially spliced HIV RNAs. Using a Rev:MS2 phage coat protein fusion that could be targeted to bind and activate the Rev-responsive element (RRE) RNA or heterologous MS2 phage operator RNA, we analyzed the role(s) of the arginine-rich RNA binding domain in RNA binding and transactivation. The arginine-rich domain could be functionally replaced by a stretch of nine arginines. However, polyarginine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…The tight correlation between in vitro binding and RNA export data (Figure 6F) suggests that the primary role of Rev oligomerization may simply be to enhance RNA-binding affinity. Consistent with this view are the findings that a single Rev NES is sufficient to mediate nuclear export (Wen et al, 1995) and that unspliced mRNAs can be exported even without Rev oligomerization if a second RRE-binding domain is covalently appended to Rev (Furnes et al, 2005) or if protein-RNA affinity is enhanced using the MS2 coat protein-RNA interaction (Nam et al, 2001). This manner of forming an RNP may also be utilized by Rev for functions other than RNA export, such as translation and genome packaging.…”
Section: Discussionmentioning
confidence: 92%
“…The tight correlation between in vitro binding and RNA export data (Figure 6F) suggests that the primary role of Rev oligomerization may simply be to enhance RNA-binding affinity. Consistent with this view are the findings that a single Rev NES is sufficient to mediate nuclear export (Wen et al, 1995) and that unspliced mRNAs can be exported even without Rev oligomerization if a second RRE-binding domain is covalently appended to Rev (Furnes et al, 2005) or if protein-RNA affinity is enhanced using the MS2 coat protein-RNA interaction (Nam et al, 2001). This manner of forming an RNP may also be utilized by Rev for functions other than RNA export, such as translation and genome packaging.…”
Section: Discussionmentioning
confidence: 92%
“…Studies with chimeric Rev and RRE (Rev fused to MS2 coat-protein and RRE stem IIB replaced with the MS2-RNA) 33 - 35 and with polyvalent Rev-binding elements (e.g., stem IIB concatemers) 36 , 37 have shown that although high affinity correlates with function, affinity alone is unable to recapitulate full export activity of the Rev-RRE complex.…”
Section: Rre As a Scaffold For Rev Assembly And Functionmentioning
confidence: 99%
“…In support of this hypothesis, we have shown for example that polyQ or polyA repeats can mediate interactions between proteins that contain them (e.g., Fiumara et al, 2010 ; Pelassa et al, 2014 ), while polyproline (polyP)-II structures and proline-rich sequences can mediate protein-protein interactions by binding to non-repetitive interaction domains (Yu et al, 1994 ). Evidence exists that some charged AARs may also drive protein-nucleic acid and protein-lipid interactions (Dean, 1983 ; Nam et al, 2001 ; DeRouchey et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%